2018
DOI: 10.1027/0269-8803/a000181
|View full text |Cite
|
Sign up to set email alerts
|

An ERP Investigation of Object-Scene Incongruity

Abstract: Abstract. The present study investigated the temporal dynamics of the object-scene congruity during a categorization task of objects embedded in a scene. Participants (n = 28) categorized objects in scenes as natural or man-made while event-related brain potentials (ERPs) were recorded. The object-scene associations were either congruous (e.g., a tent in a field) or incongruous (e.g., a fridge in a desert). The results confirmed that contextual congruity affects item processing in the 300–500 ms time window wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The N400 effect observed at the nouns in the home dialect of Experiment 1 had a broad scalp distribution, which was more frontally distributed relative to the standard central-parietal N400 effect observed in the other dialect conditions. Though more frontally distributed, this negativity effect was classified as N400 since it peaked around 400 ms, given that previous studies have also reported similar more frontally distributed N400 effects (Balconi & Caldiroli, 2011;Guillaume, Tinard, Baier, & Dufau, 2016;Kelly, Ward, Creigh, & Bartolotti, 2007;Nakano, Saron, & Swaab, 2010). The scalp distribution difference observed across the three dialect conditions in the present study suggests some differences in the neural basis of the N400 effects during lexical prediction, which needs to be examined further.…”
Section: The Facilitating Effect Of Semantic Context On the Processing Of Newly Available Wordssupporting
confidence: 53%
“…The N400 effect observed at the nouns in the home dialect of Experiment 1 had a broad scalp distribution, which was more frontally distributed relative to the standard central-parietal N400 effect observed in the other dialect conditions. Though more frontally distributed, this negativity effect was classified as N400 since it peaked around 400 ms, given that previous studies have also reported similar more frontally distributed N400 effects (Balconi & Caldiroli, 2011;Guillaume, Tinard, Baier, & Dufau, 2016;Kelly, Ward, Creigh, & Bartolotti, 2007;Nakano, Saron, & Swaab, 2010). The scalp distribution difference observed across the three dialect conditions in the present study suggests some differences in the neural basis of the N400 effects during lexical prediction, which needs to be examined further.…”
Section: The Facilitating Effect Of Semantic Context On the Processing Of Newly Available Wordssupporting
confidence: 53%
“…We used these separate and simultaneous presentations as a key manipulation to examine in what measure any semantic consistency effect requires low-level, perceptual relationships between the context and the object within the same image, or may arise exclusively from high-level guidance, independently from the actual and reciprocal organization of the context and the object in a unique percept. Moreover, and importantly, the simultaneous image presentation avoided any possible bias related to a priming effect (semantic preactivation) which may occur with sequential presentations (see also e.g., 7,15,16 ). Previous research has reported a semantic consistency categorization advantage for separate and simultaneous object images 26,27 , even after correcting for response bias, which appeared to explain only part of the effect 28 .…”
mentioning
confidence: 99%
“…This suggestion can explain the widely-reported disadvantage in identifying incongruent objects, both with respect to accuracy (e.g., Biederman et al, 1974;Boyce et al, 1989;Underwood, 2005) and to reaction times (e.g., Davenport & Potter, 2004;Palmer, 1975;Rieger et al, 2008). It is further strengthened by EEG findings, showing that the waveforms induced by congruent and incongruent scenes start to diverge in the N300 time window (200-300 ms after the scene had been presented) -if not earlier (Guillaume, Tinard, Baier, & Dufau, 2016), at which these matching procedures presumably take place, prior to object identification (Mudrik et al, 2010;Mudrik, Lamy, et al, 2014;Võ & Wolfe, 2013; though see Ganis &Kutas, 2003 andDemiral et al, 2012). Note however, that this model holds the ITC as the locus of object-context integration, at which the information from the PHC and PFC converge.…”
Section: Neural Correlates Of Object-context Integrationmentioning
confidence: 81%